2004
DOI: 10.1093/ndt/gfh585
|View full text |Cite
|
Sign up to set email alerts
|

The short- and long-term impact of multi-disciplinary clinics in addition to standard nephrology care on patient outcomes

Abstract: This analysis of outcomes in two different countries suggests that despite equal and long exposure to nephrology care prior to dialysis, there appears to be an association of survival advantage for those patients exposed to formalized clinic care in addition to standard nephrologist follow-up. While other known predictors of survival such as adequacy of dialysis and severity of illness measures were not included in the model, those parameters require time on dialysis to be accumulated. Thus, the data do sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
122
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(133 citation statements)
references
References 23 publications
2
122
0
9
Order By: Relevance
“…• surveys/audits (n = 4) surveys/audits of current care provision [135][136][137][138] • evaluation studies (n = 13) evaluating single services or comparing different services [139][140][141][142][143][144][145][146][147][148][149][150][151] • descriptive studies (n = 7) describing single services, groups of services, individual specialties within services or an intervention for care [152][153][154][155][156][157][158] Chapter 5…”
Section: Resultsmentioning
confidence: 99%
“…• surveys/audits (n = 4) surveys/audits of current care provision [135][136][137][138] • evaluation studies (n = 13) evaluating single services or comparing different services [139][140][141][142][143][144][145][146][147][148][149][150][151] • descriptive studies (n = 7) describing single services, groups of services, individual specialties within services or an intervention for care [152][153][154][155][156][157][158] Chapter 5…”
Section: Resultsmentioning
confidence: 99%
“…In all, 27.84% of CKD patients were scattered in other departments, such as inpatient wards (e.g., internal medicine wards, surgery wards) in the hospital. [9,10] Similarly, we found in the study that 18 disciplines and departments, such as the nephrology department, cardiology department, endocrinology department, and surgery department, were related to CKD patients, which provided some clinical basis and evidence for MDC. It is our belief that MDC should be helpful to these CKD patients.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies of PCP-specialist collaboration in the care of other illnesses such as diabetes and mental illnesses revealed that good patient-specialist interaction, insurance coverage, and specialist efforts to return the mutual patient to primary care were of major importance to PCPs (11) and that effective PCP-specialist communication was associated with patients' improved clinical outcomes (10). Prior studies assessing the potential benefit of multidisciplinary care (12)(13)(14) for patients with CKD did not specifically address the ongoing role of PCPs in care, nor did they specify physicians' desired content of collaboration. Although collaborative models of care are being encouraged within the nephrology community, little information has been available to inform their development (8,(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not assess physicians' attitudes regarding some important aspects of collaboration, including the management and/or prevention of common risks among patients with CKD (e.g., cardiovascular disease or prevention of acute kidney injury), the quality of information exchange between PCPs and nephrologists, or the role of other types of health care providers (e.g., nurses) in collaboration (10,(12)(13)(14). We also did not assess some physician characteristics (e.g., board certification, salary status) that could influence physicians' willingness to collaborate.…”
Section: Discussionmentioning
confidence: 99%